Romantic Concerns About Toxicity and Public Health: Literary Exploration of Contaminated Environment and the Significance of Literature in Historical Toxicology - Aftab, Hariz; Rahaman, Valiur (South Eastern European Journal of Public Health, 2024)
Poems of William Blake, William Wordsworth, S. T. Coleridge, Lord Byron, P. B. Shelley, and their contemporaries are freighted with allusions to the contaminated environment during the industrial revolution and post Tambora eruption (1815), reflective of socio-environmental realities of the Romantic period and their concerns about public health. This paper endeavors to examine Romantic poetry and assess early 19th-century toxic English landscapes to comprehend how environmental contamination was culturally perceived during this period. The study follows a critical convergence design between historical toxicology and Romantic literature for the synthesis of scientific analysis to reveal the thematic preoccupations of Romantic writing. Findings of the study demonstrate substantial references to the impact of direct release of industrial toxins into atmosphere and Tambora eruption’s toxic fallout. Literary engagements such as these foreground profound socio-ecological ramifications of toxic pollutants and offer richer insights for modern environmental policy-making and sustainable development. The study also follows an interdisciplinary approach to serve as a resource for the integrative analysis presented here and benefit the future research from its insights in filling out the understanding of how early 19th-century poets approached industrial and volcanic pollution.